Long-Term Consequences of Misdiagnosis of Parathyroid Adenomas in Pediatric Patients - Dorota Roztoczyńska; Aleksander Konturek; Anna Wędrychowicz; Magdalena Ossowska; Alicja Kapusta; Anna Taczanowska-Niemczuk; Jerzy B. Starzyk (Case Reports in Pediatrics)
Primary hyperparathyroidism (PHPT) is rare in children but exhibits a more dynamic course than in adults, often leading to multiorgan complications if diagnosis is delayed. This article aims to highlight diagnostic challenges of parathyroid adenomas in children and discuss associated complications from delayed diagnosis. Three boys, aged 15.5, 10, and 16 years, were retrospectively analyzed for hypercalcemia. The diagnosis was based on biochemical and hormonal tests, as well as imaging studies (ultrasound, scintigraphy, and densitometry). The mean diagnosis delay was 20 months (9–35). All boys experienced appetite loss and bone symptoms. Patient 1 was initially misdiagnosed with slipped capital femoral epiphysis (SCFE) and underwent orthopedic surgery without recognition of severe hypercalcemia. Patient 2 was misdiagnosed with vasopressin deficiency following a tibia fracture. Patient 3’s symptoms were attributed to stress. All patients had parathyroid adenomas, but Patients 2 and 3 had an ectopic thymus location. Following adenoma excision, Patients 2 and 3 developed hypocalcemia, the lasting consequences of which included nephrocalcinosis and low bone mass; Patient 3 also developed hypertension and depression. Conclusions: (1) any child presenting symptoms such as loss of appetite, abdominal pain, weight loss, depression, or bone abnormalities must urgently have serum calcium levels assessed to exclude PHPT. (2) Delayed diagnosis of PHPT in children is dangerous, as it leads to irreversible organ damage, including severe bone loss, nephrocalcinosis, and hypertension. (3) Comprehensive hormonal and genetic evaluation prior to surgery is essential, along with prompt correction of hypocalcemia to minimize complications and improve treatment outcomes. (4) After parathyroid adenoma removal, intensive calcium and vitamin D supplementation is required to prevent hungry bone syndrome and support proper bone recovery. (5) Due to the significant risk of disease recurrence, children with PHPT require long-term endocrine follow-up and thorough genetic testing, enabling early detection of relapse and timely intervention.